The Influence of Motivation and Training Entrepreneurship on The Performance of SME Entrepreneurs Modulated by Organizational Culture - Hairunisya, Nanis; Arifin, Syaiful; Endayani, Fatmasari; Puspasari, Meinar (Program MM Universitas Surabaya, 2024)
Purpose: This research aims to determine the relationship between motivation, entrepreneurship training and performance, as well as organizational culture as a moderator variable. Method: Respondents numbered 113 SMEs, former TKI who had received entrepreneurship training from the Manpower Service. Primary data was collected using a questionnaire and processed using PLS model path analysis assisted by the SmartPLS 3.0 program. Result: The research results are as follows: (1) Motivation has no effect on performance; (2) Entrepreneurship training influences performance; (3) organizational culture influences performance; (4) organizational culture as a moderating predictor variable has a significant effect on performance but is unable to moderate the influence of motivation and entrepreneurship training on the performance of SME entrepreneurs. The impact of entrepreneurship motivation and training may vary depending on other factors, such as stakeholder interests and local culture. These last two variables could be opportunities for further research.